Forecasting recessions using the yield curve - Marcelle Chauvet; Simon Potter (Federal Reserve Bank of New York, 2001)
We compare forecasts of recessions using four different specifications of the probit model: a time-invariant conditionally independent version, a business cycle specific conditionally independent model, a time-invariant probit with autocorrelated errors, and a business cycle specific probit with autocorrelated errors. The more sophisticated versions of the model take into account some of the potential underlying causes of the documented predictive instability of the yield curve. We find strong evidence in favor of the more sophisticated specification, which allows for multiple breakpoints across business cycles and autocorrelation. We also develop a new approach to the construction of real time forecasting of recession probabilities.
Keywords: 330; Recession Forecast; Yield Curve; Structural Breaks; Bayesian; Classical Methods; Konjunkturprognose; Kapitalertrag; Zinsstruktur; Theorie; USA